0 votes

Given that$, x:y:z = \frac{1}{2}:\frac{1}{3}:\frac{1}{4}$

$\Rightarrow x:y:z = \frac{1}{2} \times 12:\frac{1}{3}\times 12:\frac{1}{4}\times 12 \quad [{\color{Blue}{\because \text{LCM(2,3,4) = 12}}}]$

$\Rightarrow x:y:z = 6:4:3 = k\;\text{(let)}$

$\Rightarrow \boxed{x = 6k, y = 4k, z = 3k}$

$\therefore$ The value of $\dfrac{x+z-y}{y} = \dfrac{6k+3k-4k}{4k} = \dfrac{5k}{4k} = 1.25.$

Correct Answer $:\text{B}$

$\Rightarrow x:y:z = \frac{1}{2} \times 12:\frac{1}{3}\times 12:\frac{1}{4}\times 12 \quad [{\color{Blue}{\because \text{LCM(2,3,4) = 12}}}]$

$\Rightarrow x:y:z = 6:4:3 = k\;\text{(let)}$

$\Rightarrow \boxed{x = 6k, y = 4k, z = 3k}$

$\therefore$ The value of $\dfrac{x+z-y}{y} = \dfrac{6k+3k-4k}{4k} = \dfrac{5k}{4k} = 1.25.$

Correct Answer $:\text{B}$